Implementing cloud design patterns for AWS : create highly efficient design patterns for scalability, redundancy, and high availability in the AWS Cloud /: create highly efficient design patterns for scalability, redundancy, and high availability in the AWS Cloud. (2015) - Young, Marcus
No abstract available